Production and characterization of a polyclonal antibody of anti-rLipL21-IgG against Leptospira for early detection of acute leptospirosis - Seenichamy, Arivudainambi; Bahaman, Abdul Rani; Abdul Mutalib, Abdul Rahim; Bejo, Siti Khairani (Hindawi Publishing Corporation, 2014)
Leptospirosis is one of the zoonotic diseases in animals and humans throughout the world. LipL21 is one of the important surface-exposed lipoproteins in leptospires and the most effective cross protective immunogenic antigen. It is widely considered as a diagnostic marker for leptospirosis. In this study, we evaluated the serodiagnostic potential of LipL21 protein of Leptospira interrogans serovar Pomona. We have successfully amplified, cloned, and expressed LipL21 in E. coli and evaluated its specificity by immunoblotting. Purified recombinant LipL21 (rLipL21) was inoculated into rabbits for the production of polyclonal antibody. Characterization of the purified IgG antibody against rLipL21 was performed by cross reactivity assay. Only sera from leptospirosis patients and rabbit hyperimmune sera recognized rLipL21 while the nonleptospirosis control sera showed no reaction in immunoblotting. We confirmed that anti-rLipL21-IgG antibody cross reacted with and detected only pathogenic leptospiral species and it did not react with nonpathogenic leptospires and other bacterial species. Results observed showed that anti-rLipL21-IgG antibody has high specificity and sensitivity to leptospires. The findings indicated that the antibody could be used in a diagnostic assay for detection of leptospires or their proteins in the early phase of infection.